Baseline anemia and its associated factors among adult cancer patients at Northwest Amhara Regional State Referral Hospitals, Northwest Ethiopia, 2021 - Wassie, Yilkal Abebaw; Zegeye, Alebachew Ferede; Gebrehana, Deresse Abebe; Tsega, Sintayehu Simie; Kibralew, Getasew; Fentahun, Setegn; Setegn, Abebaw; Nakie, Girum (Frontiers in Oncology, 2024)
Introduction: Currently, the problem of cancer has been increasing in the world, predominantly in middle and low income countries. Anaemia is a principal and overwhelming health problem, has a significant burden upon cancer patients and can cause distortion of patient's quality of life.Different articles reported that the magnitude of anemia was prevalent among adult patients with cancer. Despite this, as per the investigators' knowledge, there is little data known about the problem in Ethiopia.Objective: This study aimed to assess the prevalence of baseline anemia and associated factors among adult cancer patients at Northwest Amhara comprehensive Specialized Hospitals, oncology treatment units, Northwest Ethiopia, 2021.Methods: An institutional-based cross-sectional study was conducted in Northwest Amhara Comprehensive Specialized Hospitals. A systematic random sampling technique was used to select 315 participants. The data were collected using interviewer-administered and chart review through structured, pretested questionnaires. The data were entered into Epi. Data version 4.6 and analyzed using Stata version 14.0. Bivariable and multivariable logistic regression was carried out to identify factors associated with anemia. Adjusted odds ratio with 95% confidence interval and variables with a p-value< 0.05 were considered significantly associated with anemia.The prevalence of baseline anemia among adult patients with cancer was found to be 34.84 %. Being females (AOR= 1.97, 95%, CI: 1.00-3.87), being underweight (AOR=1.96, 95% CI: 1.09-3.52) and patients with stage III cancer (AOR=2.35, 95% CI: 1.12-3.01) were significantly associated with anaemia.The prevalence of baseline anemia among adult cancer patients was significant.Being female, cancer patients with underweight body mass index and clinical-stage III cancer patients were associated with baseline anemia. It's better to give special attention to female patients, patients with underweight, and advanced-stage cancer patients to reduce the risk of developing the outcome.